Effectiveness of Using Indonesian in Writing Scientific Papers - Pertiwi, Tri (Inspiring Law Journal, 2024)
In writing scientific papers, the language used must be scientific language. This means that the language is in accordance with the applicable rules of writing language. This is to reduce differences in perception between the writer and the reader which will cause miscommunication between the writer and the reader. Based on the discussion of the effectiveness of sentences in scientific papers, it can be concluded that writers of scientific papers pay less attention to the effectiveness of the sentences used. This is evidenced by the many ineffective sentences found in scientific papers produced by students and lecturers. This ineffectiveness is caused by sentences that are not commensurate, not parallel, not economical, not careful, and not logical because they are not careful in using words